(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: effective control of cardiovascular risk factors remains low in most countries and also in Germany. We investigate whether socio-economic status has an impact on the level of medical treatment and control (normalized values) of total cholesterol. Methods: data on blood lipids from 4 892 participants in the last German Health Survey of 1998 are analysed, adjusting for key determinants in logistic regression analyses. Socio-economic status is not determined by educational achievement alone but also including occupation and household income. Results: the actual prevalence of total cholesterol of ≥240 mg/dl was 53.4%. Only 3.6% of prevalent cases are under effective treatment. Less favourable values of total cholesterol and HDL are displayed by males and in lower social groups, while the middle groups are in an intermediate position. Chances to be treated for hypercholesterolemia are significantly less favourable for females (odds ratio (OR) estimate: 0.70) and better for the age bands ≥50 (OR 2.37) and ≥60 (OR 3.57), if a general practitioner is visited (OR 1.77), and if living in Eastern Germany (OR 1.89). However, chances are not significantly different according to social status. Conclusions: statistically significant social group differences cannot be detected at the present low level of effective treatment. This may be different if higher levels of control are achieved.